EVALUATION OF ANTI-DIABETIC ACTIVTY OF DIFFERENT EXTRACTS OF MYRISTICA FRAGRANS HOUTT: IN VITRO AND IN SILICO STUDIES - Sivaraj, Saranya; Kannayiram, Gomathi; Dasararaju, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:Â This study is aimed to evaluate the anti-diabetic effect of sequentially extracted (hexane, dichloromethane, ethyl acetate, and ethanol) Myristica fragrans houttÂ (mace) through in vitroÂ and in silicoÂ studies. Methods:Â The in vitroÂ anti-diabetic effect of the sequentially extracted plant were evaluated for its alpha-amylase inhibitory activity and the potential binding was studied by in silicoÂ studies using SchrÃ¶dinger Maestro. Results:Â All extracts showed dose dependent alpha-amylase inhibitory effect. At concentration 500 Âµg/ml, all the extracts showed more than 60% inhibition of the alpha-amylase enzyme and the highest inhibition (81.30%) at 500Â Âµg/ml was observed in DCM extract of mace. Potential compounds were identified by in silicoÂ molecular docking studies of alpha-amylase with phytocomponents fromÂ DCM extract. Among the top threeÂ compoundsÂ from virtual screening, induced fit docking studies revealed 2,5-bis(3,4-dimethoxyphenyl)-3,4-dimethyloxolaneÂ possessed better binding affinity when compared with the drug metformin. Conclusion:Â The obtained in vitroÂ and in silicoÂ results suggest that all extracts of Myristica fragrans can be used successfully for the management of diabetes mellitus. Keywords: Myristica fragrans, Mace, Sequential extraction, Alpha-amylase, Molecular docking.